2016
DOI: 10.3168/jds.2016-10921
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Holstein calves fed whole milk with or without kefir

Abstract: A growing body of evidence suggests health-promoting effects of kefir consumption on different nonruminant species, leading to the speculation that kefir may act as a probiotic and benefit calf performance and health. Our objectives were to determine effects of feeding kefir on performance and health of calves in the first 70d of life. Thirty 3-d-old female Holstein calves (body weight=38.2±3.1kg) were blocked by initial body weight and assigned randomly to 1 of 3 treatments (1 calf per pen; 10 pens per treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The developing rumen of the dairy calf provides a potential opportune period to direct microbial establishment (Yáñez-Ruiz et al, 2015). Early dietary interventions, probiotics, and adult rumen contents have been used in an attempt to modify the rumen and fecal microbial communities of young ruminants (Schönhusen et al, 2003; Ishaq et al, 2015; Fouladgar et al, 2016; Zhang et al, 2017). Rumen contents inoculated into calves have included the use of mixed ruminal microbiota from either whole rumen fluid or a ruminal bolus.…”
Section: Introductionmentioning
confidence: 99%
“…The developing rumen of the dairy calf provides a potential opportune period to direct microbial establishment (Yáñez-Ruiz et al, 2015). Early dietary interventions, probiotics, and adult rumen contents have been used in an attempt to modify the rumen and fecal microbial communities of young ruminants (Schönhusen et al, 2003; Ishaq et al, 2015; Fouladgar et al, 2016; Zhang et al, 2017). Rumen contents inoculated into calves have included the use of mixed ruminal microbiota from either whole rumen fluid or a ruminal bolus.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, its regular consumption has been related to many health benefits (Ahmed et al 2013). Moreover, Fouladgar et al (2016) showed that the intake of kefir by neonatal calves improved productivity and health. The antioxidant capacity of kefir could be due to its protondonating ability, its reducing power, and SODlike activity (Liu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In dairy industry, calf diarrhea has been causing considerable economic losses because of calf mortality, weight loss in surviving calves all over the world, including Hokkaido. Several probiotics have been used as preventive or supportive therapy for dairy cattle and neonatal calf for a long time, and previous reports indicated the bene t calf performance and health [14][15][16][17][18][19][20][21][22][23][24][25]. Fermented milk, an old probiotics for dairy cattle, provides several clinical bene ts for calf breeding, and has been widely used as economical and safe probiotics [26][27][28].…”
Section: Discussionmentioning
confidence: 99%